Plasma Kisspeptin Levels in Girls with Premature Thelarche - Akinci, Aysehan; Cetin, Dilek; Ilhan, Nevin (Galenos Yayincilik, 2012)
Objective: Premature thelarche (PT) is defined as isolated breast development without secondary sex characteristics in girls below the age of eight. We aimed to determine whether the level of kisspeptin, which plays a role in the release of gonadotropins, is associated with PT. Methods: The patient group included children with PT aged 3-8 years (n=20) and the control group included healthy children in the same age range (n=20). Height standard deviation scores (HSDSs), bone maturation and growth velocity were evaluated in the two groups. Basal follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), prolactin (PRL), and sex hormone-binding globulin (SHBG) levels were also measured in the two groups by immunochemiluminometric assay (ICMA). A gonadotropin-releasing hormone (GnRH) test was also conducted in the patient group and the peak levels of FSH and LH were determined. Kisspeptin levels were measured using enzyme immunoassay (EIA). Results: No differences were found between the groups in terms of age, HSDS, annual growth rate and bone age. While the plasma basal FSH, LH and E2 levels in the patient and control groups did not show statistically significant differences, PRL levels were higher in the patient group (p<0.05). Peak LH response to GnRH test was at the prepubertal level (<5 ng/mL) in patients with PT. In the patient group, kisspeptin levels were significantly higher compared to the levels in the control group (2.96+/-1.21 ng/dL vs. 1.19+/-0.41 ng/dL; p<0.05), and kisspeptin levels showed a significant correlation with PRL, FSH, LH, and E2 levels (p<0.05). Conclusions: In this study, plasma kisspeptin levels were found to be higher in patients with PT and to show a positive correlation with increased PRL levels. Kisspeptin is one of the neuropeptides that plays a role in the onset of puberty. Our results support the hypothesis that PT may result from the temporary activation of central stimulants.
Keywords: Kisspeptin; premature thelarche